The Impact of The Environment and Leadership Patterns on Employee Work Achievement At Uptd Region Viii Samsat Langsa - Eryani, Eryani (International Journal of Language and Ubiquitous Learning, 2023)
Background. This study describes the impact of the environment and leadership patterns on employee work achievement at the Technical Implementation Unit (UPTD) region VIII of the Langsa samsat. Purpose. The purpose of this study is to educate readers and measure the extent of environmental impact and work achievement patterns of employees. Method. This study uses multiple linear regression analysis methods, used to determine the independent variable on the dependent variable. Researchers used the help of the SPSS (Statistical Product and Service Solution) program so that the results obtained were more directed. The number of samples studied was 21 respondents. The analysis used includes percentage calculation, partial test (t-test), correlation test, significance test and coefficient of determination test. Results. The results of the study found that the impact of the environment and leadership patterns on the achievement of employee work at UPTD region VIII samsat Langsa is in good criteria with the results of the analysis reaching factors that affect performance, namely the leadership variable has an average of 4.56 and the work environment variable has an average of 4.39. In addition, based on the hypothesis which states that there is a significant effect of leadership on employee performance, it is proven to be true in the partial test (t test) the t-count result for the leadership variable is 1.867 and the value in the 5% distribution table is 1.697. And partially the work environment variable has more influence on employee performance with the results of t count 4.987. Conclusion. The conclusion of research at UPTD region VIII Samsat Langsa, it can be concluded that leadership and work environment have a significant effect on employee performance. Leadership has a positive influence, while the work environment is more dominant in influencing employee performance, indicated by a higher t value.